Prospects of increase of management efficiency by innovative activity of domestic enterprises - Yepifanova, I. Yu. (Visnyk of Vinnytsia Politechnical Institute, 2013)
The essence of the process of innovation management companies is considered in the paper. Stages of industrial innovation are estimated. Ways of increasing the effectiveness of management innovation of domestic enterprises are formed.